The Drug Targets and Antiviral Molecules for Treatment of Ebola Virus Infection - Wu, Wenjiao; Liu, Shuwen (Current Topics in Medicinal Chemistry, 2017)
Ebola virus (EBOV) is a highly pathogenic virus causing severe hemorrhagic fever with a high case fatality rate of 50% - 90% in humans. Without an approved vaccine or treatments, Ebola outbreak management has been limited to palliative care and barrier methods to prevent transmission. These approaches, however, have yet to end the 2014 outbreak of Ebola after its prolonged presence in West Africa. As with the increase of outbreaks, a significant effort has been made to develop promising countermeasures for the prevention and treatment of Ebola virus infection. In this review, development of therapeutics and potential inhibitors for Ebola virus infection will be discussed.
Keywords: Vaccines and antibody